Development of Traditional Snack Selection Simulation App Based on MDLC as Nutritional Literacy Media for Housewives - Muhammad Arif Putra Ramadhan; Cholid Mawardi; Yudha Pradana (Universitas Teknokrat Indonesia, 2026)
The increasing prevalence of Non-Communicable Diseases (NCDs) such as hypertension and diabetes in Indonesia is closely linked to excessive consumption of Sugar, Salt, and Fat (GGL). Despite government regulations, nutritional literacy among housewives who act as primary household food providers remains low, particularly in understanding complex nutritional labels on traditional snacks. This research aims to develop a nutritional literacy medium titled